HEALTH LITERACY AND ORAL HEALTH BEHAVIORS DECREASE THE RISK OF ORAL FRAILTY IN JAPANESE ELDERLY. (11th November 2018) - Nishimoto, M; Tanaka, T; Hirano, H; Kikutani, T; Watanabe, Y; Ohara, Y; Huruya, H; Iijima, K
Abstract: Aim: As the cumulative risks of poor oral health, so-called ORAL FRAILTY, for adverse health outcomes have recently received considerable attention, identifying predictors of oral frailty is essential. Continuous maintenance of oral health is required to prevent tooth loss and dental diseases; its routine practice, however, depends on individual habits and abilities. Therefore, improving both health literacy (HL) and oral health behaviors may prevent oral frailty. We aimed to clarify whether HL and oral health behaviors decrease the risk of oral frailty among community-dwelling elderly. Methods: A total of 821 Japanese elderly (72.1 ± 5.2 years old; 47% women) were randomly selected from disability-free residents in Kashiwa City. They participated in the baseline survey in 2012, and follow-up surveys in up to 2016 (4 years). Oral frailty, which was determined by six-item according to previous report, was assessed in 2012–2016. Communicative and critical health literacy (CCHL), tooth brushing habits, and dental visits were examined by self-reported questionnaire. Results: At baseline, the mean value of CCHL was 4.0 (±0.6); 81% of participants brushed their teeth ≥2 times daily; 74% annually visited a dentist. During follow-up, 40% of participants had new-onset of oral frailty. Participants with higher CCHL or brushing teeth ≥ 2 times daily showed significantly decreased risk of oral frailty [adjusted hazard ratios (95% confidence interval): 0.73 (0.55–0.98); 0.83 (0.69–0.99), respectively]. Conclusions: Both high HL and tooth brushing might be associated with new-onset of oral frailty, suggesting that improving these factors routinely could contribute to prevention of oral frailty.